Effect of Threshold Pressure Gradients on Control Areas Determination of Production Well in CBM Reservoirs. (18th December 2019) - Wang, Ruifei; Yang, Jiaosheng; Wang, Meizhu; Zhao, Yang; Chen, Weiqing
Abstract : Understanding the mechanism of water drainage and gas recovery is the burning issue for Coalbed Methane (CBM) reservoir development. In the process of exploitation, threshold pressure gradients (TPG) is an important factor affecting the control areas, which related to the low-permeability and complex water saturation of CBM reservoirs. In this paper, a new flow model of CBM has been established considering the TPG and gas desorption. Then we carried out a series of experiments and fitted out a new relational expression between TPG and permeability and water saturation, which shows that TPG is negatively correlated with permeability and positively correlated with water saturation. After that, we analyzed the influence of TPG and desorption on the control radius and illustrated a case study. The results show that TPG and desorption effect both can slow down the rate of pressure reduction. The case study indicates that the control radius of target well groups ranges from 55 m to 136.7 m The average control radius and gas TPG are 91.3 m 0.0082 MPa/m respectively. Furthermore, we classify the wells into 5 categories, which are mainly distributed in III (80∼100 m). Finally, we suggest using well pattern infilling in region II and III and hydraulic fracturing method for region IV to increase the utilization area and the sustainability for the target area. This study provides a quick and reasonable prediction of control radius in CBM reservoir with different water saturation for further adjustment suggestion and sustainable development.